Faktor-faktor yang Mempengaruhi Terhadap Kriminalitas di Indonesia - Juni Adri Kasma; Yollit Permata Sari (Universitas Negeri Padang, 2024)
Crime is a problem that is always experienced and cannot be easily avoided in various countries, both developed and developing countries. Indonesia is a country with a crime rate that is comparable to the United States, Iraq and Columbia, which occupy the top 3 positions of countries with high crime rates in the world. There are various factors that influence the high crime rate in Indonesia, such as income inequality, poverty, unemployment and minimum wages. This type of research is quantitative research using provincial data in Indonesia for 2014 - 2022. The data analysis technique uses panel data regression techniques with the help of e-views software. The results of the research show that income inequality has no significant effect on the crime rate in Indonesia, the poverty level has a positive and significant effect on the crime rate in Indonesia, unemployment and the provincial minimum wage has a negative and very significant effect on the crime rate. crime in Indonesia.